Role of METTL3-mediated m6A modification in osteogenic differentiation of periodontal ligament stem cells extracted from adult periodontal ligaments ex-vivo: Effect of METTL3 on periodontal ligament stem cells - Yao, Chun; Xin, Haiyan; Liu, Si; She, Peng; Ma, Yanhong; Hu, Min; Jin, Yan (Cellular and Molecular Biology, 2023)
Periodontal ligament stem cells (PDLSCs) are identified as candidate cells for the regeneration of periodontal and alveolar bone tissues. This research was to analyze the effect of methyltransferase-like 3 (METTL3)-mediated m6A modification on the osteogenic differentiation of PDLSCs extracted from adult periodontal ligaments (PDLs) ex-vivo. From June 2022 to October 2022, 27 patients undergoing orthodontic treatment in our hospital were selected as the research population, with 31 teeth extracted in total. PDLSCs were isolated from PDLs by tissue block culture, and the results were analyzed. Then PDLSCs were induced to differentiate into osteoblasts, and changes in METTL3 and m6A levels during differentiation were observed. Additionally, abnormal METTL3 expression vectors were constructed and transfected into PDLSCs to observe the influence of METTL3 on the biological behavior and osteogenic differentiation of PDLSCs. PDLSCs isolated from ex-vivo PDLs were predominantly spindle-shaped, with high CD73, CD90 and CD105 levels and low CD11b, CD34 and CD45 levels, showing the characteristics of stem cells. Spearman correlation coefficients identified a positive connection between Runx2, Sp7, Alp, Bglap, METTL3 and m6A levels and osteogenic differentiation incubation time (P<0.05). As METTL3 expression was increased, the proliferation capacity and osteogenic differentiation ability of PDLSCs were enhanced (P<0.05), and the content of m6A was increased (P<0.05). However, the activity and osteogenic differentiation ability of PDLSCs was decreased after silencing METTL3 (P<0.05). In conclusion, METTL3-mediated m6A modification promoted the osteogenic differentiation of PDLSCs extracted from adult PDLs ex vivo. This study offered a novel understanding of the mechanisms underlying osteogenic differentiation, and implied a possible method for accelerating bone formation.